Faktor-Faktor yang Memengaruhi Persepsi Petani alam Penggunaan Psb (Photosynthetic Bacteria) Sebagai Stimulan Pertumbuhan Tanaman Padi Sawah - Febrimeli, Dwi; Suherma, Mita; Herawaty, Herawaty (Hasanuddin University, 2025)
The use of Photosynthetic bacteria (PSB) as a growth stimulant for rice plants to increase productivity is new for farmers. The purpose of this study is to analyze the level of farmer perception and the factors that influence farmer perception in the use of PSB. This study was conducted from March to June 2024. Data collection methods were unstructured interviews and questionnaires that had been tested for validity and reliability. The data analysis method used was a Likert scale and multiple linear regression. The results of the study showed that the level of farmer perception in the use of PSB as a growth stimulant for rice plants was classified as moderate, with a percentage of 57.6%. This indicates that farmers have begun to accept and understand the use of PSB as a rice plant stimulant. Farmer perceptions are influenced by factors of knowledge, land area, cosmopolitanism, innovation characteristics, and intensity of extension, but the factor that has a very significant influence is the social environment.